Pengaruh Retention Pajak, Profitabilitas Dan Leverage Terhadap Kinerja Laba (Studi Kasus Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2019) - Anti Endah Lestari; Chairil Anwar Pohan (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study discussed Tax Retention, Profitability, and Leverage on Profit Performance. The purpose of this study was to analyze the effect of Tax Retention, Profitability, and Leverage on Profit Performance. The research method used was a quantitative approach. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange in 2016-2019. The determination of the sample was conducted by using the purposive sampling method. Based on the results of the study, it was shown that tax retention had a significant effect with tcount by 4.421, the profitability on return on assets (ROA) had no significant effect with tcount by 1.535, the profitability on return on equity (ROE) had a significant effect with tcount by 2.409, the leverage on debt to assets ratio (DAR) had no significant effect with tcount by 0.418, the leverage on debt to equity ratio (DER) had no significant effect with tcount by 1.274. The results of the simultaneous test (F test) determined the Fcount value of 12,592 with a significance value (0.000 <0.05) so that the hypotheses stated that Tax Retention, Profitability and Leverage had an effect on Profit Performance were accepted. The simultaneous effect was equal to (36%).